Преобразуйте в многочлен два выражения: (2х+1)(х-4) (х-3)(х+5)(х-3)(х-5)

Анастасия20010104 Анастасия20010104    3   27.07.2019 21:10    1

Ответы
Lerka0tarelka Lerka0tarelka  03.10.2020 14:40
(2x + 1)(x - 4) = 2x^2 - 8x + x - 4 = 2x^2 - 7x - 4

(x - 3)(x + 5)(x - 3)(x - 5) = (x - 3)^2 (x - 5)(x + 5) = 
= (x^2 - 6x + 9)(x^2 - 25) = 
= x^2 (x^2 - 25) - 6x(x^2 - 25) + 9(x^2 - 25) = 
= x^4 - 25x^2 - 6x^3 + 150x + 9x^2 - 225 = 
= x^4 - 6x^3 - 16x^2 + 150x - 225 
ПОКАЗАТЬ ОТВЕТЫ
Другие вопросы по теме Алгебра